DSP techniques for implementation of perfectly matched layer for truncating FDTD domains - Ramadan, O; Oztoprak, AY (Iee-Inst Elec Eng, 2002)
A new algorithm for implementing the perfectly matched layer (PML) using digital signal processing (DSP) is presented for truncating finite difference time-domain (FDTD) domains. The algorithm is based on incorporating digital filtering techniques into the PML formulation. A simple. unsplit-field and material independent PML formulation is achieved.
Keywords: Pml; Media